(untitled) (Revista de Psicología, 2019)
The purpose of the study was to examine the relationship between the Ryff’s multidimensional psychological well-being model and the five-factor model of personality in college students. In order to do this, 315 undergraduate students from the Universidad de Concepción (Chile) completed the Psychological Well-Being Scales and the Big Five Inventory. As predicted, psychological well-being and its dimensions were inversely related to Neuroticism and directly related to the remaining factors. Likewise, it was found that Consciousness and Neuroticism had the highest influence on psychological well-being. Also were found gender differences in Neuroticism, Concientiousness and Agreeableness.